Tree lucerne management and utilization - Aberra, Adie; Getahun, Elizabeth; Bezabih, Melkamu; Worku, Tigist (International Livestock Research Institute, 2024)
Tree lucerne is a multipurpose fodder tree adapted to the highlands of Ethiopia. It is widely used as livestock feed in Basona Werena and neighbouring woredas (districts) of North Shewa Zone.